Functional Properties of Gelatin/Konjac Glucomannan-Based Coatings with Aomori Hiba Essential Oil and Their Effect on Ethylene Production in Peach Fruit (Prunus persica (L.) Batsch cv. ‘Hikawa Hakuho’) during Cold Storage - TANAKA, Fumihiko; TANAKA, Fumina; HAGIWARA, Shoji; KOGA, Arisa; WIGATI, Laras Putri (Environment control in biology, 2024)
Aomori hiba essential oil (AO) inhibits ethylene production in fruit and vegetables. In this study, the properties of gelatin (GE)/konjac glucomannan (KGM)-based coatings and films incorporating 5%, 25%, and 50% (w/w of polymer) AO were investigated. The base of the coating solution (GK) was a mixture of 1% (w/v) GE solution and 1% (w/v) KGM solution at a ratio of 7:3. The AO/GK films showed extremely low gas permeability to O2 and CO2 compared to general modified atmosphere packaging. The microstructures of the AO/GK films observed via scanning electron microscopy (SEM) indicated a reduction in the barrier properties of the films due to pores formed by the volatilization of AO. The effect of the AO/GK coating on ethylene production in peaches (Prunus persica (L.) Batsch, cv. ‘Hikawa Hakuho’) during cold storage was also examined. The surface of the coated peach skin was covered with the coating and the stomata were sealed. The GK coating without AO and with low concentrations of AO suppressed ethylene production during storage at 10℃. Based on these results, we concluded that AO5/GK is the most applicable coating agent for maintaining the freshness of fruits and vegetables.